Between dictatorship and democracy : Russian post-communist political reform - McFaul, Michael, 1963-; Petrov, Nikolaĭ (Nikolaĭ Vladimirovich); Ri͡abov, Andreĭ (Washington, D.C. : Carnegie Endowment for International Peace, 2004)
For hundreds of years, dictators have ruled Russia. Do they still' In the late 1980s, Soviet President Mikhail Gorbachev launched a series of political reforms that eventually allowed for competitive elections, the emergence of an independent press, the formation of political parties, and the sprouting of civil society. After the collapse of the Soviet Union in 1991, these proto-democratic institutions endured in an independent Russia. But did the processes unleashed by Gorbachev and continued under Russian President Boris Yeltsin lead eventually to liberal democracy in Russia' If not, what kind of political regime did take hold in post-Soviet Russia' And how has Vladimir Putin's rise to power influenced the course of democratic consolidation or the lack thereof' Between Dictatorship and Democracy seeks to give a comprehensive answer to these fundamental questions about the nature of Russian politics.
Introduction / Michael McFaul, Nikolai Petrov, and Andrei Ryabov -- Elections / Michael McFaul and Nikolai Petrov -- The Constitution / Viktor Sheinis -- Legislative-executive relations / Andrei Ryabov -- Political parties / Michael McFaul -- Civil society / Michael McFaul and Elina Treyger -- The mass media / Andrei Ryabov -- The rule of law / Mikhail Krasnov -- Federalism / Nikolai Petrov -- Regional models of democratic development / Nikolai Petrov -- Public attitudes about democracy / Vladimir Petukhov and Andrei Ryabov.
Includes bibliographical references and index.
Vendor-supplied metadata.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Russia (Federation) -- Politics and government -- 1991-; Democracy -- Russia (Federation); Post-communism -- Russia (Federation); Russie -- Démocratie.; Postcommunisme -- Russie; Russie -- Politique et gouvernement -- 1991-2000.; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Democracy; Politics and government; Post-communism; Russia (Federation); Politieke hervormingen; Postcommunisme; 89.40 internal relations of the state: general; Demokratisierung; Politische Reform; Russland; Democracy -- Russia (Federation); Post-communism -- Russia (Federation); Russia (Federation) -- Politics and government -- 1991-; Russia -- Politics and government -- 1991-; Since 1991